2012
DOI: 10.1002/bmc.2751
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of sitagliptin and simvastatin in human plasma by LC‐MS/MS and its application to a human pharmacokinetic study

Abstract: A simple, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method has been developed and validated for simultaneous quantification of sitagliptin and simvastatin in human plasma. Carbamazepine was used as an internal standard (IS). The analytes and IS were extracted from the human plasma by liquid-liquid extraction technique. The reconstituted samples were chromatographed on an Alltima HP C(18) column using an isocratic solvent mixture [acetonitrile-5 mm ammonium acetate (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Several LC-MS/MS method have been reported for the estimation of sitagliptin in biological matrices, such as plasma, urine and hemodialysate. The majority of the reported methods are used in clinical applications (Zeng et al, , 2010Nirogi et al, 2008;Hess et al, 2011;Bonde et al, 2013;Burugula et al, 2013;Reddy et al, 2015;Scherf-Clavel and Högger, 2015) compared with preclinical applications (Yao et al, 2011;Gananadhamu et al, 2012;Patel et al, 2014). Shantikumar et al (2015) reported an LC-QTOF/MS method for the determination of five gliptins (vildagliptin, saxagliptins, sitagliptins, linagliptins and teneligliptin) in clinical application.…”
Section: Hplc Coupled With Ms/ms Detectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several LC-MS/MS method have been reported for the estimation of sitagliptin in biological matrices, such as plasma, urine and hemodialysate. The majority of the reported methods are used in clinical applications (Zeng et al, , 2010Nirogi et al, 2008;Hess et al, 2011;Bonde et al, 2013;Burugula et al, 2013;Reddy et al, 2015;Scherf-Clavel and Högger, 2015) compared with preclinical applications (Yao et al, 2011;Gananadhamu et al, 2012;Patel et al, 2014). Shantikumar et al (2015) reported an LC-QTOF/MS method for the determination of five gliptins (vildagliptin, saxagliptins, sitagliptins, linagliptins and teneligliptin) in clinical application.…”
Section: Hplc Coupled With Ms/ms Detectionmentioning
confidence: 96%
“…Patel et al (2014) reported a simple protein precipitation using MeOH which was free from matrix effect and gave high recovery and simple extraction. Nirogi et al (2008) and Burugula et al (2013) described various methods to quantitatively determine the plasma concentrations in human plasma using LLE using a combination of TBME, dichloromethane and n-hexane as extraction solvent. A C 18 column was used to measure sitagliptin concentrations from human plasma; it gives good peak shape, resolution and reproducibility.…”
Section: à80°cmentioning
confidence: 99%
“…Literature reports highlights that few methods for quantification of gliptins (except teneligliptin) [8][9][10] are available. It also demonstrates poor recovery and sensitivity of vildagliptin and saxagliptin because of non-specific binding 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different methods based on spectrophotometry [20,21]; spectrofluorometry [21,22]; capillary electrophoresis [23]; HPLC [24][25][26]; UPLC [27] and LC-MS/MS [28][29][30][31] were also developed for the quantification of sitagliptin in single as well as in multidrug component formulations including metformin. Linagliptin was reported to be quantitatively analyzed using HPLC [32] and LC-MS/MS [33,34] techniques.…”
Section: Introductionmentioning
confidence: 99%